UHPLC-MS-MS analysis of oxylipins metabolomics components of follicular fluid in infertile individuals with diminished ovarian reserve - Chengcheng Liang; Xiaole Zhang; Cong Qi; Hui Hu; Qinhua Zhang; Xiuxian Zhu; Yonglun Fu (BMC, 2021)
Abstract Background Diminished ovarian reserve (DOR) refers to a decrease in the number and quality of oocytes in the ovary, which results in a lack of sex hormones and a decline of fertility in women. DOR can potentially progress to premature ovarian failure (POF), which has a negative impact on women's quality of life and is a major cause of female infertility. Oxidative stress is a major contributor to fertility decrease in DOR patients, affecting the follicular microenvironment, oocyte maturation, fertilization, and embryo development. Understanding intracellular signal transduction can be achieved by defining specific oxidized lipid components in follicular fluid (FF) of DOR infertile patients. Methods The oxylipins metabolic signatures in the FF of DOR patients and females with normal ovarian reserve (NOR) enrolled for the in vitro fertilization (IVF) cycle were analyzed using UHPLC-MS-MS technology. Principal component analysis (PCA) and orthogonal projections to latent structure discriminant analysis (OPLS-DA) were used to analyze the derived metabolomic profiles. Pathway enrichment analysis was carried out using the Kyoto Encyclopedia of Genes and Genomes (KEGG) and MetaboAnalyst databases. Furthermore, the Spearman rank correlation coefficient was used to determine the correlation between age, FSH, AMH, AFC, oocytes retrieved, MII oocytes, fertilization, high-quality embryos, and the concentration of differential oxidized lipid metabolites in FF. Results Fifteen oxylipins metabolites were found to be lower in the FF of DOR patients than those in the NOR group, including ±20-HDoHE, ±5-iso PGF2α-VI, 12S-HHTrE, 15-deoxy-Δ12,14-PGJ2, 1a,1b-dihomo PGE2, 1a,1b-dihomo PGF2α, 20-COOH-AA, 20-HETE, 8S,15S-DiHETE, PGA2, PGD2, PGE1, PGF1α, PGF2α, and PGJ2. The pathway enrichment analysis revealed that the 15 differentially oxidized lipid metabolites were closely related to the arachidonic acid metabolic pathway. Correlation analysis revealed that the concentration of 8 different oxidized lipid metabolites in FF was negatively correlated to FSH and positively correlated with AFC. AMH, the number of oocytes retrieved, MII oocytes and fertilization, were all positively correlated with 9 different oxidized lipid metabolites, but only one metabolite was positively correlated with the number of high-quality embryos. Conclusions Metabolomic analysis of FF revealed that oxylipins metabolism disorders were closely related to ovarian reserve function. Among these oxylipins metabolites, arachidonic acid metabolism undergoes significant changes that may be related to oocyte development, resulting in decreased fertility in DOR patients. Trial registration ChiCTR, ChiCTR2000038182 , Registered 12 September 2020-Retrospectively registered